Surgical Management of Heterotaxy Syndrome: Current Challenges and Opportunities. Issue 2 (March 2020) - Alongi, Ashlyn M.; Kirklin, James K.; Deng, Luqin; Padilla, Luz; Pavnica, Jozef; Romp, Robb L.; Mauchley, David C.; Cleveland, David C.; Dabal, Robert J.
Introduction: Heterotaxy syndrome presents a unique challenge in surgical management, even in the current era. We hypothesized that certain anatomic subsets merit novel strategies. Methods: We analyzed morphologic details, surgeries, comorbidities, subsequent admissions, and survival using Kaplan-Meier methods and multivariable risk models from a single-institution experience of 103 consecutive patients with heterotaxy who underwent cardiac surgery between January 1, 1990, and May 31, 2016. Results: Of the 103 patients (50 males and 53 females), 31 had left atrial isomerism, 64 had right atrial isomerism (RAI), and 8 patients' isomerism was indeterminate (IND), with first cardiac operation at a mean 1.0 year (standard deviation ±3.0 years) of age. Kaplan-Meier overall survival estimate was 83.1% at six months, 77.8% at one year, 65.9% at five years, and 52.1% at ten years. Survival was particularly low among RAI following repair of total anomalous pulmonary venous connection (TAPVC) at first operation, with one- and five-year survival of 57% and 46%, respectively. By multivariable analysis, the only risk factor for death during the early phase (hazard model) was repair of TAPVC at the first cardiac operation (hazard ratio [HR]: 4.4, P = .01), and risk factors during the longer term constant phase were atrioventricular valve (AVV) regurgitation (HR: 4.2, P < .01), male gender (HR: 3.7, P < .01), and two-ventricle repair (HR: 3.0, P = .02). Patients with heterotaxy undergoing the Fontan procedure had excellent subsequent survival (85% at ten years). Conclusions: This analysis of over 100 patients with heterotaxy identified TAPVC requiring initial repair as the major risk factor for early death and important AVV regurgitation as the major risk factor in the longer term. Survival with RAI and early repair of TAPVC were poor, with one-year mortality exceeding 40%. Patients with single ventricle completing the Fontan operation enjoyed outstanding ten-year survival (85%). Initial management of RAI requiring early repair of TAPVC remains challenging. For this high-risk subset, alternative strategies such as early referral for cardiac transplantation evaluation warrant consideration.